EVALUATION OF PEEL EXTRACT OF MANGOSTEEN AS A DYE NATURAL AND ANTIOXIDANT AND ITS USE AS AN ADDITIVE IN A FRUIT BEVERAGE - Machado, Y. J.; Murillo-Arango, W.; Hennessey-Ramos, L. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was aimed to evaluate the antioxidant capacity, the phenolic content, the dye stability, the yield of extracts of different polarities obtained from the peel of mangosteen (Garcinia Mangostana), and finally, their potential use as an additive in mangosteen fruit beverage. Water, ethanol, and different mixtures were used to obtain the dye extracts. Physicochemical and microbiological stability was measured according to Colombian Resolution 3929 of 2013 to determine whether the beverage complies with current regulations. CIE L*a*b* scale measured the color stability of the beverage for 30 days, the sensorial acceptance with a hedonic scale. The best extraction performance was achieved with the mixture of water and ethanol in a 1:1 ratio, yielding 23.07 ±0.12% of total biomass extracted from the peel, and the phenolic content was 368.7 mg GAE 100 mL-1, IC50 values of 184 mg mL-1, and 146 mg mL-1 by the ABTS and DPPH respectively. The beverage prepared from mangosteen pulp and dye extract reached the microbiological requirements by Resolution 3929 of 2013 for fruit drinks. The sensorial test showed that formulated mangosteen beverage dye extract is hedonically the same at treatment with ascorbic acid.